Not all scalar inferences are alike: The effect of existential presuppositions - Amiraz, Omri (Proceedings of the Amsterdam Colloquium, 2022)
This paper investigates a novel puzzle regarding the indirect scalar inference (SI) ‘not all’ ⇝ ‘some’. When ‘not all’ is embedded in a Strawson-Downward-Entailing context, some constructions give rise to more robust SIs than others even though they express the same proposition with the same lexical items. I argue that this contrast is related to whether or not the quantifier phrase occurs in a conventionalized focus construction. If it does, the SI is not derived by implicature calculation but arises from an existential presupposition triggered by the focus construction. Hence, it is not sensitive to contextual considerations.